Conservation status and reproduction of the critically endangered freshwater pearl mussel (Margaritifera margaritifera) in Northern Ireland. Issue 4 (8th November 2012) - Reid, Neil; Keys, Alan; Preston, Jane S.; Moorkens, Evelyn; Roberts, Dai; Wilson, Conor D.
ABSTRACT: Freshwater unionoids are one of the most threatened animal groups worldwide and the freshwater pearl mussel Margaritifera margaritifera is currently listed as critically endangered in Europe. The EC Habitats Directive requires that EU Member States monitor the distribution and abundance of this species and report regularly on its conservation status. The pearl mussel meta‐population in Northern Ireland was surveyed to assess temporal population trends in Special Areas of Conservation (SACs) and mussel reproduction throughout its range. Mussels occurred in six rivers and numbers within three SAC designated sites remained stable between 2004–2007 and 2011. The discovery of more than 8000 previously unknown individuals in the Owenreagh River contributed to an overall increase (+56.8%) in the total known population. All populations actively reproduced during 2010 with approximately half of all individuals gravid. Moreover, suitable salmonid hosts occurred at all sites with 10.7% of salmon and 22.8% of trout carrying encysted glochidia. Populations were composed entirely of aged individuals with little evidence of recent recruitment. It is inferred that the break in the life cycle must occur during the juvenile stage when glochidia metamorphose and settle into the interstitial spaces within the substrate. Water quality parameters, most notably levels of suspended solids, exceeded the recommended maximum thresholds in all rivers. It is posited that the deposition of silt may be the main cause of juvenile mortality contributing to a lack of recruitment. Consequently, all populations were judged to be in 'unfavourable' conservation status. Catchment‐level management plans are urgently needed to reduce siltation with the aim of improving recruitment. These results have implications for the success of ex situ conservation programmes; specifically, the size at which captive‐bred juveniles are released into the wild. Further research is required to assess the vulnerabilities of early life‐stages of M. margaritifera to siltation. Copyright © 2012 John Wiley & Sons, Ltd.